Online Social Network Analysis. - Fang, Binxing; Jia, Yan; Publishing House of Electronics Industry (Online Social Network Analysis ;, 2019)
The three volume set provides a systematic overview of theories and technique on social network analysis. Volume 3 of the set mainly focuses on the propagation models and evolution rules of information. Information retrieval and dissemination, topic discovery and evolution, algorithms of influence maximization are discussed in detail. It is an essential reference for scientist and professionals in computer science.